2010
DOI: 10.2202/1557-4679.1205
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Feedback in Bayesian Regression Adjustment for the Propensity Score

Abstract: McCandless, Gustafson and Austin (2009) describe a Bayesian approach to regression adjustment for the propensity score to reduce confounding. A unique property of the method is that the treatment and outcome models are combined via Bayes theorem. However, this estimation procedure can be problematic if the outcome model is misspecified. We observe feedback that can bias propensity score estimates. Building on new innovation in Bayesian computation, we propose a technique for cutting feedback in a Bayesian prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 13 publications
0
54
0
Order By: Relevance
“…Despite relatively infrequent use in orthopedics propensity scores have become popular especially in the area of the epidemiological analysis of treatment effects. 9 The generalized propensity score determines the probability of receiving a particular treatment based on a variety of variables. 5 Our hypothesis that surgeons can impact graft choice was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite relatively infrequent use in orthopedics propensity scores have become popular especially in the area of the epidemiological analysis of treatment effects. 9 The generalized propensity score determines the probability of receiving a particular treatment based on a variety of variables. 5 Our hypothesis that surgeons can impact graft choice was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods described as “quasi-Bayesian,” “approximately-Bayesian,” or “two-step Bayesian” have been recently proposed to combine estimation of the propensity score with that of causal effects without appealing to Bayes theorem to unify these two stages with a joint likelihood (Hoshino, 2008; McCandless et al, 2010; Kaplan and Chen, 2012; Zigler and Dominici, 2014). These methods have been described as “cutting the feedback” between the propensity score and outcome stages (Lunn et al, 2009), and represent a special case of so-called “modularization” in Bayesian inference (Liu et al, 2009).…”
Section: Bayesian Estimation Of Causal Effects With Propensity Scoresmentioning
confidence: 99%
“…While the usefulness of propensity scores for Bayesian inference was motivated decades ago (Rubin, 1985), the promise of modern Bayesian analysis tools has spawned renewed interest in Bayesian estimation of causal effects with propensity scores (Hoshino, 2008; McCandless et al, 2009; An, 2010; McCandless et al, 2010; Kaplan and Chen, 2012; Zigler et al, 2013; McCandless et al, 2012; Zigler and Dominici, 2014; Saarela et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Zigler et al (2013) assessed the joint estimation of the Bayesian propensity score and the treatment effect and found that the feedback between propensity score model and outcome model can lead to poor treatment effect estimates. This model feedback is especially problematic if the relationship between the outcome and the propensity score is misspecified (McCandless, Douglas, Evans, & Smeeth, 2010 (2010) included the posterior distribution of the propensity score parameters as covariate input in the outcome model so that the flow of information between the propensity score and the outcome is restricted. This so-called sequential Bayesian propensity score analysis yields treatment effect estimates that are comparable to estimates obtained from frequentist propensity score analysis.…”
Section: Bayesian Propensity Score Approachmentioning
confidence: 99%